Siri Diges Kemanusiaan: Membedah Lautan Hikmah - Shuhairimi, Abdullah (editor) (Penerbit UniMAP, 2019)
Books order can be made directly to UniMAP Press, Universiti Malaysia Perlis. (penerbitan@unimap.edu.my / 04 9775159)